Identification of individuals and groups in a public goods experiment - Sven Christens; Astrid Dannenberg; Florian Sachs (Philipps-University Marburg, School of Business and Economics, 2017)
Revealing the identities of contributors has been shown to increase cooperation in public goods games. In this paper we experimentally investigate whether this finding holds true when decisions are made by groups rather than individuals. We distinguish between groups in which members can discuss face-to-face to reach a decision and groups in which members communicate via computer chat. The results confirm the positive effect of identification on cooperation among individuals. For groups, however, we only find a small and temporary effect of identification, irrespective of the type of communication. The reason for this is that the sensitivity to others' opinions plays an important role for individual decisions but not for group decisions.
Keywords: C72; C91; C92; H41; 330; public goods experiment; cooperation; group decisions; face-to-face communication; computer chat communication; identification; shame